A dietary intervention with conjugated linoleic acid enhances microstructural white matter reorganization in experimental stroke - Straeten, Frederike A.; Strecker, Jan-Kolja; Börsch, Anna-Lena; Maus, Bastian; Hoppen, Maike; Schmeddes, Birgit; Härtel, Lucia; Fleck, Ann-Katrin; van Zyl, Stephanie; Straeten, Tabea; Beuker, Carolin; Koecke, Mailin; et al. (Frontiers in Neurology, 2024)
Background A dietary supplementation with conjugated linoleic acid (CLA) was shown to attenuate inflammation and increase the proportions of circulating regulatory T cells (Tregs) and M2-type macrophages in disease models such as autoimmune encephalitis and arteriosclerosis. Since Tregs and anti-inflammatory (M2-type) macrophages were found to enhance stroke recovery, we hypothesized that CLA-supplementation might improve stroke recovery via immune modulatory effects. Methods Functional assessment was performed over 90 days after induction of experimental photothrombotic stroke in wild type mice (n = 37, sham n = 10). Subsequently, immunological characterization of different immunological compartments (n = 16), ex vivo magnetic resonance (MR, n = 12) imaging and immunohistochemical staining (n = 8) was performed. Additionally, we tested the effect of CLA in vitro on peripheral blood mononuclear cells from human stroke patients and healthy controls (n = 12). Results MR diffusion tensor imaging (DTI) demonstrated enhanced microstructural reorganization of interhemispheric white matter tracts, dependent on lesion size. Functional recovery over 90 days remained unaffected. Detailed immunological analyses across various compartments revealed no significant long-term immunological alterations due to CLA. However, analyses of human blood samples post-stroke showed reduced levels of pro-inflammatory interferon-γ (IFN-γ) and tumor necrosis factor alpha (TNF-α) release by T-lymphocytes following in vitro treatment with CLA. Conclusion We aimed to explore the efficacy of a dietary intervention with minimal known side effects that could be accessible to human stroke patients, regardless of the degree of disability, and without the risks associated with aggressive immunomodulatory therapies. Our main findings include improved microstructural reorganization in small infarcts and a reduced inflammatory response of human T cells in vitro.